FACTORS AFFECTING SKEPTICISM TOWARD GREEN ADVERTISING: A STUDY OF UNIVERSITY STUDENTS IN JAKARTA - Huang, Jacky; Darmayanti, Dahlia (Bina Nusantara University, 2014)
The number of green advertising has been increasing recently due to the concern toward the environment. This research aims to examine if there is correlation between environmental concern, conservation behavior, and buying behavior toward skepticism against green advertising claims. Survey was used to collect data from 150 respondents through paper questionnaire. Cronbach’s Alpha and Confirmatory Factorial Analysis are utilized to determine reliability and validity of the constructs. Multiple Linear Regressions are the hypothesis testing chosen for this study. Independent T-Test is performed to differentiate consumers’ skepticism level toward green advertising claims in relation to the gender group. Cross-tabulation analysis is also performed in order to find out if there is correlation between age and expense toward skepticism level. The result concluded that Environmental Concern was positively affecting the skepticism level of a consumer toward green advertising claims. The finding also shows that environmental behavior of a consumer does not have significant relation to the level of skepticism toward green advertising claims. Environmental Concern of a consumer produce most significant influence toward skepticism level against green advertising claims. However, environmental behavior of consumers does not affect consumers being skeptical toward green advertising claims.